2022
DOI: 10.1111/jfpp.16572
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of lupin milk with soy milk as an alternative egg substitute for cake production

Abstract: This study was aimed to produce low-egg cake by replacing 0%, 25%, 50%, and 75% of egg used in cake production with legume milk obtained from soy and lupin. Some physical, chemical, and sensory properties of the cakes prepared with the different replacement ratios of legume milk were determined. Cakes containing soy milk gave higher amounts of ash, fat, total phenolic content (TPC), antioxidant activity, Ca, K, Mg, and P compared to lupin milk substituted cakes. Crust and crumb L* and b* values of cakes prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…), followed by Europe which comfortably occupies second place (32.1%, 396 k ha), then Africa (5.4%, 66 k ha), with America having close data (4.6%, 57 k ha); in last place is Asia (<1%, 108 ha). From the geographical point of view, it is possible to group the included articles by origin continents: Europe [ 50 , 51 , 53 , 55 , 59 , 63 , 70 , 72 , 73 , 75 ], South America [ 54 , 58 , 61 , 66 ], Asia [ 47 , 56 , 60 , 64 , 65 , 68 , 69 , 74 , 77 , 78 ], Africa [ 49 , 52 , 62 , 67 , 71 , 76 , 79 ] and Oceania [ 48 , 57 ]. This grouping revealed that Europe and Asia are, for now, the leading promoters of these novel food products, and Africa also reports many studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…), followed by Europe which comfortably occupies second place (32.1%, 396 k ha), then Africa (5.4%, 66 k ha), with America having close data (4.6%, 57 k ha); in last place is Asia (<1%, 108 ha). From the geographical point of view, it is possible to group the included articles by origin continents: Europe [ 50 , 51 , 53 , 55 , 59 , 63 , 70 , 72 , 73 , 75 ], South America [ 54 , 58 , 61 , 66 ], Asia [ 47 , 56 , 60 , 64 , 65 , 68 , 69 , 74 , 77 , 78 ], Africa [ 49 , 52 , 62 , 67 , 71 , 76 , 79 ] and Oceania [ 48 , 57 ]. This grouping revealed that Europe and Asia are, for now, the leading promoters of these novel food products, and Africa also reports many studies.…”
Section: Discussionmentioning
confidence: 99%
“…To divide the products developed by categories, the following terms were determined: meat alternatives [ 47 ], dairy alternatives [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], grains [ 56 , 57 , 58 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ], snacks [ 70 , 71 , 72 , 73 , 74 , 75 , 76 ] and desserts [ 77 , 78 , 79 ]. The grain category has the most results, and it can be subdivided into terms such as bread making [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ], enriched pasta [ 63 , 64 , 65 , 66 ] and traditional foods [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations